An evaluation of the relationships between poverty and HIV/AIDS in Kwa-Langa, Cape Town - Ndabula, Sipho Theodore (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2008.